2018
DOI: 10.3892/mmr.2018.8983
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas�gingivalis induced inflammatory responses and promoted apoptosis in lung epithelial cells infected with H1N1 via the Bcl‑2/Bax/Caspase‑3 signaling pathway

Abstract: The aim of the present study was to investigate the effects of Porphyromonas gingivalis (P. gingivalis) on inflammatory cytokine and nitic oxide (NO) production in lung epithelial cells infected with H1N1, and the underlying mechanisms. Lung epithelial cells were co-infected with P. gingivalis and H1N1. The concentrations of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6 were detected via an ELISA, and the concentration of NO was detected by the nitrate reductive enzymatic method at 4, 8, 12 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…5c). As mentioned in the literature review, the Bcl2/ Bax/caspase3 pathway is an important apoptosis pathway 54 , and our results confirmed that ASF1B disruption mediated by shRNA caused cervical cancer cell apoptosis in this way. Subsequently, we further confirmed that ASF1B and CDK9 are the factors of a nuclear complex to promote cervical cancer progression by co-IP and colocalization of ASF1B and CDK9 in the nucleus (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…5c). As mentioned in the literature review, the Bcl2/ Bax/caspase3 pathway is an important apoptosis pathway 54 , and our results confirmed that ASF1B disruption mediated by shRNA caused cervical cancer cell apoptosis in this way. Subsequently, we further confirmed that ASF1B and CDK9 are the factors of a nuclear complex to promote cervical cancer progression by co-IP and colocalization of ASF1B and CDK9 in the nucleus (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…As an opportunistic pathogen, P. gingivalis cannot be completely eliminated by host cells. An in vitro study suggested that during co-infection of P. gingivalis and influenza virus, significant apoptosis and necrosis can be observed in lung epithelial cells within a short timeframe ( Connolly et al, 2017 ) as the Bcl2/Bax/Caspase3 signaling pathway was activated ( Chen et al, 2018 ). Cytotoxic products of P. gingivalis (e.g., lipopolysaccharide) can induce host cells release of inflammatory cytokines such as TNF-α, IL-1β, and IL-6 ( Ke et al, 2016 ), which in turn increase NO production leading to lung epithelial cell damage ( Alayan et al, 2006 ; Wu et al, 2016 ; Ahamed et al, 2017 ).…”
Section: Interaction Between Oral Microbiome and Virus Infectionmentioning
confidence: 99%
“…Furthermore, P. gingivalis might affect pneumonia progression through interactions with other respiratory pathogens. Co-infection of P. gingivalis and H1N1 in lung epithelial cells promoted the production of inflammatory CKs and NO, resulting in increased levels of apoptosis via the Bcl-2/Bax/caspase-3 pathway [ 111 ]. P. gingivalis can modulate Pseudomonas aeruginosa -induced respiratory epithelial cell apoptosis via the STAT3 signaling pathway by causing transient inhibition and, ultimately, exerting promoting effects [ 112 ].…”
Section: Respirologymentioning
confidence: 99%